2018
DOI: 10.1016/s1470-2045(18)30081-0
|View full text |Cite
|
Sign up to set email alerts
|

Axitinib in combination with pembrolizumab in patients with advanced renal cell cancer: a non-randomised, open-label, dose-finding, and dose-expansion phase 1b trial

Abstract: Pfizer Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
214
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 324 publications
(230 citation statements)
references
References 33 publications
(43 reference statements)
8
214
0
8
Order By: Relevance
“…This finding led to discontinuation of further study of these combinations in clinical trials . In contrast, axitinib a more selective inhibitor of the vascular endothelial growth factor receptor with a lower known risk for hepatotoxicity as a single agent compared to sunitinib or pazopanib, demonstrated a lower rate of severe hepatotoxicity …”
Section: Clinical Trials Of Icis: Results Of Risk For Hepatotoxicitymentioning
confidence: 99%
“…This finding led to discontinuation of further study of these combinations in clinical trials . In contrast, axitinib a more selective inhibitor of the vascular endothelial growth factor receptor with a lower known risk for hepatotoxicity as a single agent compared to sunitinib or pazopanib, demonstrated a lower rate of severe hepatotoxicity …”
Section: Clinical Trials Of Icis: Results Of Risk For Hepatotoxicitymentioning
confidence: 99%
“…These monoclonal antibodies targeting immune checkpoints (PD1 and PD-L1), by their role in restoring the antitumor immunity through the reversal of immune escape or evasion, have led to a significant antitumor activity with confirmed impact on the duration of tumor response and prolonged overall survival. They have earned fast approvals across multiple cancer subtypes including melanoma, lung cancer, urological tumors, breast cancer and other solid tumors [16][17][18][19][20]. More importantly, these agents have earned several indications as monotherapy without association to chemotherapeutic agents, thus predisposing cancer patients to a different and more tolerable toxicity profile [16,17,19,21].…”
Section: Role Of Icis In Cancermentioning
confidence: 99%
“…In a phase I study, PD‐L1 blockade with atezolizumab showed promising antitumor activity with a manageable safety profile . Recent clinical trials for advanced RCC seemed to focus on combination therapy . They included combination regimens with two ICIs, such as nivolumab plus ipilimumab, and those with ICIs and angiogenesis inhibitors, such as pembrolizumab plus axitinib, and avelumab plus axitinib …”
Section: Biomarkers For Immune Checkpoint Therapymentioning
confidence: 99%